A new species of Lakshmia Yakovlev, 2004 (Lepidoptera: Cossidae) from Northern Thailand with a world catalogue of the genus - Yakovlev, Roman V.; Nakao, Kenichiro (Zootaxa, 2013)
A cossid genus Lakshmia Yakovlev, 2004, was established by an original designation of the type species, Lakshmia zolotuhini Yakovlev, 2004. Among the genera within the subfamily Zeuzerinae Boisduval, [1828], this genus is closely related to Phragmataecia Newman, 1850 (type species: Noctua arundinis Hübner, [1808]), Butaya Yakovlev, 2004 (type species: Butaya gracilis Yakovlev, 2004) and Yakovlevina Kemal & Koçak, 2005 (type species: Garuda galina Yakovlev, 2004). Diagnostic characters of Lakshmia include the presence of an ochreous brown band on the forewing, the elongate valvae with parallel edges, and a greatly reduced saccus in the male genitalia. Lakshmia comprise four species collected from Northern Thailand and Southern Vietnam (Yakovlev 2004, 2006, 2011; Fig. 1). All known specimens of Lakshmia were collected at light. Their biology is unknown. While curating specimens of Cossidae collected from Thailand, the second author (KN) found one male which was identified as a new species and thus is described in this article.